2018
DOI: 10.1111/jnc.14572
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic function of the gephyrin‐binding protein IQSEC3 regulates neurotransmitter‐specific matching of pre‐ and post‐synaptic structures in primary hippocampal cultures

Abstract: In dissociated neuronal cultures the absence of spatial and temporal cues causes the emergence of mismatched synapses, where post-synaptic proteins of GABAergic synapses are in part apposed to glutamatergic pre-synaptic terminals and vice versa. This mismatch offers an opportunity to study the mechanisms that regulate correct apposition of pre- and post-synaptic elements. We report here that the IQ motif and Sec7 domain-containing protein 3 (IQSEC3; BRAG3; synArfGEF) specifically regulates the mislocalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…BIG3 (brefeldin A-inhibited guanine nucleotide exchange protein 3) was reported to specifically regulate GABAergic synaptic transmission (Liu et al, 2016). More recently, overexpression of a dominant-negative, GTP binding-defective ARF6-T27N mutant was shown to recapitulate the phenotype of IQSEC3 E749A in cultured neurons, exhibiting mismatched apposition of pre-and postsynaptic structures (Fruh et al, 2018), consistent with our data (Figure S4). These observations suggest the intriguing possibility that ARF signaling pathways are involved in modulating activity-dependent Figure S3).…”
Section: Discussionsupporting
confidence: 90%
“…BIG3 (brefeldin A-inhibited guanine nucleotide exchange protein 3) was reported to specifically regulate GABAergic synaptic transmission (Liu et al, 2016). More recently, overexpression of a dominant-negative, GTP binding-defective ARF6-T27N mutant was shown to recapitulate the phenotype of IQSEC3 E749A in cultured neurons, exhibiting mismatched apposition of pre-and postsynaptic structures (Fruh et al, 2018), consistent with our data (Figure S4). These observations suggest the intriguing possibility that ARF signaling pathways are involved in modulating activity-dependent Figure S3).…”
Section: Discussionsupporting
confidence: 90%
“…However, IQSEC3 was not identified in a recent GABA A R γ2‐subunit pull down study 5 . Nonetheless, IQSEC3 is clearly involved in the organization of GABAergic synapses, in particular, the correct alignment of the GABAergic pre‐ and postsynaptic compartments 23 . Curiously, we also identified IQSEC2, a known constituent of excitatory postsynaptic densities, 26 in GlyR α1β complexes.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have also revealed the co‐localization of IQSEC3 with GPHN, GABA A Rs, and GlyRs at inhibitory synapses in mouse retina 22 and biochemical interactions with GPHN 21,23 . Labelling with iBioID using Bira‐GPHN demonstrated the presence of IQSEC3 in the vicinity of GPHN within GABAergic synapses 24 .…”
Section: Discussionmentioning
confidence: 83%
“…We next sought to determine whether loss of ARF6 induces network dysfunctions, which are often associated with impaired GABAergic synapse formation and function and a resulting imbalance in excitation/inhibition (E/I) ratio at synaptic and circuit levels [30,35]. To test the effect of ARF6 KD on seizure susceptibility, we employed an acute kainic acid (KA)-induced epileptic mouse model, which has been extensively used to dissect molecular mechanisms underlying initial epileptogenesis event(s) that transforms normal neural networks into hypersynchronous networks.…”
Section: Loss Of Arf6 Accelerates Seizure Susceptibility In An Arf Acmentioning
confidence: 99%
“…However, it is possible to propose that normal ARF6 function is crucial for GABAergic synapse development, as evidenced by reported actions of ARF6 GEFs and GAPs at GABAergic synapses. GIT1 regulates GABA A R trafficking and GABAergic synaptic transmission [27], whereas IQSEC3/BRAG3 directly interacts with gephyrin to regulate GABAergic synapse formation [17,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%